The Role of Advanced Foreign Experiences in Increasing the Efficiency of the Educational Process - Madina, Qobilova (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, it is mentioned about the education of citizens in Japan - the system of "moral education", "education aimed at the formation of character", "activities aimed at educating moral qualities acceptable for the state", "education of the basics of civic ethics".